RANCANG BANGUN SIMULATOR SURYA MENGGUNAKAN HIGH POWER LED - Julian; Paris Ali Topan; Masyitah Aulia; Muhammad Hidayatullah (Program Studi Teknik Elektro, 2023)
So far solar panel testing has been carried out using sunlight which is strongly influenced by weather factors. This research was conducted with the aim of designing and assembling a simple solar simulator using HPL. The method used is to combine six different colors of HPL with different convex lenses with certain tilts and angles so that the light rays can blend together . The results obtained are solar panels can produce the highest voltage value of 17.58 volts, the highest current value of 0.0140 amperes and the highest power value of 0.2430 watts with a luminance level of 900 lm. The solar simulator that was tested could not make the solar panel produce an output of 5 watts due to several factors such as the distance of the light source to the solar panel, the number of colors of the LED lights that were lit (spectrum and intensity of light), the angle of light and the lens used.